ANALISA PERHITUNGAN PERKUATAN WWTP (WASTE WATER TREATMENT PLANT) MUSIM MAS BATAM - Valentana Ardian Tarigan (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2018)
Designing on the Waste Water Treatment Plant, often overlooked by variations in water pressure at the time of empty water reservoirs suddenly, so the designing often assumes that the water load is a static load.The case reviewed on the WWTP wall structure is evident that water also has unique behavior especially in large structures. Careful planning certainly will not lead to anything like the case occurring in this research review.The repair or reinforcement analyzed through the Hydro Test testing behavior concludes that without dismantling the entire building, it can still revert to the planned needs of the WWTP building structure.The analysis performed using the finite element method tool to speed up the calculation states that by increasing the number of existing reinforcement can improve the ability of WWTP structure.